Cross-Cultural Adaptation of Darmasiswa International Students in Central Java Indonesia - Nuning Zaidah; Laily Nur Affini; Ajeng Setyorini; Siti Nur'Aini (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2023)
The research probed the cross-cultural adaptation of international students who participated in the Darmasiswa program in Indonesia. They have various cultural backgrounds; they lived in Java and interacted with Javanese cultures. The Darmasiswa students’ varied experiences brought particular attention to their competence to adapt to a host country. This study aims to discover how Darmasiswa students overcome the assimilation process, embrace the psychological elements of intercultural communication, and how they handle the adaptation process. It also seeks to discover the efforts to make this program successful and recognise how the participants deal with the challenges of adapting to the local culture. This study used a descriptive qualitative method and employed an in-depth interview to approach the research participants. The participants came from Myanmar, Japan, Singapore, India, Hungaria, Timor Leste, and Thailand. They joined the Darmasiswa program in 2019 to study and learn bahasa Indonesia, the arts, and the cultures. They studied at four universities in Semarang for one year in Central Java Province, Indonesia. Findings showed that the Darmasiswa students’ adaptation and interaction processes were varied. The culture shock experienced by the students were influenced by their family value from their home countries. Internal and external factors played an essential role in influencing the success of the Darmasiswa students’ adaptation. The factors include; communication system, symbolic interaction, social life, personal mindset, the host society's motivation, and the Darmasiswa students’ involvement with the host country’s cultural activities. Those factors affected the students' adaptation levels and learning achievement in the program.